Effects of yellow and green light stress on emergence, feeding and mating of Anomala corpulenta Motschulsky and Holotrichia parallela Motschulsky (Coleoptera: Scarabaeidae) - Jiang, Yueli; Huang, Qiuying; Wei, Guoshu; Gong, Zhongjun; Li, Tong; Miao, Jin; Lu, Ruijie; Mei, Shiqiong; Wang, Xueqin; Duan, Yun; Wu, Yuqing; Lu, Chuantao (International Journal of Agricultural and Biological Engineering, 2023)
Light is one of the key environmental factors for insects to survive. Artificial light sources different from natural environmental light can cause light stress in insects. Yellow and green light stress can interfere with the diurnal rhythm of nocturnal moths and their mating, oviposition, and adult longevity. The scarabaeid beetles Anomala corpulenta Motschulsky and Holotrichia parallela Motschulsky are widely distributed, and they are very harmful underground pests. In order to clarify the effects of light stress on their behaviors, individuals of both species were exposed to yellow light (565-585 nm) and green light (525-545 nm), with different light intensity gradients of yellow light in a laboratory setting. The short-term light stress treatment of A. corpulenta and H. parallela was carried out at night. The number of beetles emerging per half an hour was recorded, and mating pairs and feeding activity in 24 h were counted. The results showed that yellow and green light stress significantly changed the rhythm and reduced the rate of beetle emergence in the two beetle species investigated. Also, the peak emergence activity was delayed and the feeding and mating activities were significantly reduced. When treated with different intensities of yellow light, it was found that the rate of emergence of A. corpulenta under 10 lx was close to the control groups. The rate of emergence in H. parallela was significantly lower than the control groups before 0:00, in the 60 lx and 110 lx treatment groups, but after 0:00, the emergence rate of H. parallela was significantly higher in the 60 lx and 110 lx treatment groups than other treatments. However, the emergence rhythms in the three light intensity treatment groups are basically the same as in the control groups. The feeding amount and mating beetles in the three light intensity treatment groups were significantly lower than in the control groups. There were no significant differences in the three treatments. The results show that light stress above 10 lx significantly interferes with the behavioral activities of the two beetle species, investigated. This study provides a new approach for a light control technology for nocturnal beetle pest species.Keywords: yellow and green light, Anomala corpulenta Motschulsky, Holotrichia parallela Motschulsky, emergence rhythm, feeding, matingDOI: 10.25165/j.ijabe.20231601.7639Citation: Jiang Y L, Huang Q Y, Wei G S, Gong Z J, Li T, Miao J, et al. Effects of yellow and green light stress on emergence, feeding and mating of Anomala corpulenta Motschulsky and Holotrichia parallela Motschulsky (Coleoptera: Scarabaeidae). Int J Agric & Biol Eng, 2023; 16(1): 81–87.